A Novel Alu Element Insertion in ATM Induces Exon Skipping in Suspected HBOC Patients. (4th April 2023) - Klein, Janin; Allister, Aldrige B.; Schmidt, Gunnar; Otto, Annette; Heinecke, Kai; Bax-Knoche, Jördis; Beger, Carmela; Becker, Sarah; Bartels, Stephan; Ripperger, Tim; Bohne, Jens; Dörk, Thilo; et al.
Abstract : The vast majority of patients at risk of hereditary breast and/or ovarian cancer (HBOC) syndrome remain without a molecular diagnosis after routine genetic testing. One type of genomic alteration that is commonly missed by diagnostic pipelines is mobile element insertions (MEIs). Here, we reanalyzed multigene panel data from suspected HBOC patients using the MEI detection tool Mobster . A novel Alu element insertion in ATM intron 54 (ATM:c.8010+30_8010+31insAluYa5) was identified as a potential contributing factor in seven patients. Transcript analysis of patient-derived RNA from three heterozygous carriers revealed exon 54 skipping in 38% of total ATM transcripts. To manifest the direct association between the Alu element insertion and the aberrant splice pattern, HEK293T and MCF7 cells were transfected with wild-type or Alu element-carrying minigene constructs. On average, 77% of plasmid-derived transcripts lacked exon 54 in the presence of the Alu element insertion compared to only 4.7% of transcripts expressed by the wild-type minigene. These results strongly suggest ATM:c.8010+30_8010+31insAluYa5 as the main driver of ATM exon 54 skipping. Since this exon loss is predicted to cause a frameshift and a premature stop codon, mutant transcripts are unlikely to translate into functional proteins. Based on its estimated frequency of up to 0.05% in control populations, we propose to consider ATM:c.8010+30_8010+31insAluYa5 in suspected HBOC patients and to clarify its role in carcinogenesis through future epidemiological and functional analyses. Generally, the implementation of MEI detection tools in diagnostic sequencing pipelines could increase the diagnostic yield, as MEIs are likely underestimated contributors to genetic diseases.